PENGARUH INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA SELATAN TAHUN 2010-2014 - Panorama, Maya; Litriani, Erdah; Kurniasih, Lilik (I-Economics, 2019)
Infrastructure development in Indonesia has been going on for a long time and the investment has been very large. Infrastructure is an infrastructure. The availability of infrastructure is an important matter in the framework of economic developments in a region in accelerating the economic development process. Economic growth is an increase in the capacity of a long-term nation to produce various goods and services. The data used are panel data with a period from 2010 to 2014 for 17 regencies / cities in South Sumatra. To find results that are BLUE (Based Linear Unbiased Estimator), a panel test such as the Chow test and Hausman Test is conducted to complete the data with the characteristics as above. Than, tested classical assumptions such as normality, multicollinearity, heteroscedasticity, and autocorrelation. From the chow test and the best hausman test model in this study is the fixed effect model. While the results of the classic assumption test, f test t test, R2 test are from the four independent variables that have a significant effect on economic growth